Zagadnienie tzw. domów kultowych w megalitycznym obrządku pogrzebowym ludności kultury pucharów lejkowatych w Polsce - Socha, Krzysztof (Folia Praehistorica Posnaniensia, 2015)
The article is a summary of the state of the art concerning the so-called cult houses discovered in megaliths of the Funnel Beaker culture (hereinafter referred to as TRB from German Trichterbecherkultur) in its Eastern and South-Eastern groups. The author suggests to divide the discussed objects into types “A” and “B”, which may better reflect their characteristics. He also emphasises that the reinterpretation of some of the known features as the structures of this type would significantly increase their number. If the chosen course of interpretation appears accurate, it may indicate that the presence of wooden structures in the TRB graves in the Polish lands was not at all special. However, it should be borne in mind that these objects might have served not only for religious purposes.